Exogenous Silicon Enhanced Salt Resistance by Maintaining K+/Na+ Homeostasis and Antioxidant Performance in Alfalfa Leaves - Meng, Yuanfa; Yin, Qiang; Yan, Zhijian; Wang, Yuqing; Niu, Jianming; Zhang, Jie; Fan, Kai (Frontiers in Plant Science, 2020)
Silicon (Si) has been known to enhance salt resistance in plants. In this experiment, 4-weeks-old alfalfa seedlings were exposed to different NaCl concentrations (0–200 mM) with or without 2 mM Si for two weeks. The results showed that NaCl-stressed alfalfa seedlings showed a decrease in growth performance, such as stem extension rate, predawn leaf water potential (LWP) and the chlorophyll content, potassium (K+) concentration, as well as the ratio of potassium/sodium ion (K+/Na+). In contrast, NaCl-stressed alfalfa seedlings increased leaf Na+ concentration and the malondialdehyde (MDA) level, as well as the activities of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) in alfalfa leaves. Besides, exogenous Si application enhanced photosynthetic parameters of NaCl-stressed alfalfa seedlings, which was accompanied by the improvement in predawn LWP, level of chlorophyll content, and water use efficiency (WUE). The Si-treated plants enhanced salinity tolerance by limiting Na+ accumulation while maintaining K+ concentration in leaves. It also established K+/Na+ homeostasis by increasing K+/Na+ radio to protect the leaves from Na+ toxicity and thereby maintained higher chlorophyll retention. Simultaneously, Si-treated plants showed higher antioxidant activities and decreased MDA content under NaCl stress. Our study concluded that Si application enhanced salt tolerance of alfalfa through improving the leaves photosynthesis, enhancing antioxidant performance and maintaining K+/Na+ homeostasis in leaves. Our data further indicated exogenous Si application could be effectively manipulated for improving salt resistance of alfalfa grown in saline soil.